Private investment in AIDS vaccine development: obstacles and solutions - Batson Amie; Ainsworth Martha (The World Health Organization, 2001)
The development of vaccines for the prevention of AIDS, malaria, tuberculosis, and other diseases requires both public and private investment. Private investment, however, has been far lower than might have been hoped, given the massive human toll of these diseases, particularly in the poorest countries. With a view to understanding this situation and exploring potential solutions, the World Bank AIDS Vaccine Task Force commissioned a study on the perspectives of the biotechnology, vaccine, and pharmaceutical industries regarding investment in research and development work on an AIDS vaccine. It was found that different obstacles to the development of an AIDS vaccine arose during the product development cycle. During the earlier phases, before obtaining proof of product, the principal barriers were scientific. The lack of consensus on which approach was likely to be effective increased uncertainty and the risks associated with investing in expensive clinical trials. The later phases, which involved adapting, testing, and scaling up production for different populations, were most influenced by market considerations. In order to raise the levels of private research and development in an AIDS vaccine there will probably have to be a combination of push strategies, which reduce the cost and scientific risk of investment, and pull strategies, which guarantee a market.